Pharmacokinetics of valproic acid in the elderly. - Perucca, E (1984)
The kinetics of a single oral dose of sodium valproate was studied in six healthy elderly patients (age 68-89 years) and six young control subjects (age 24-26 years). The profiles of total plasma valproic acid (VPA) concentrations were very similar in the elderly and in the young. Half-lives (15.3 +/- 0.7 s.e. mean in the elderly vs 13.0 +/- 1.0 h in the young), volumes of distribution (0.16 +/- 0.01 l/kg in the elderly vs 0.14 +/- 0.01 l/kg in the young) and clearance (7.5 +/- 0.9 ml h-1 kg-1 in the elderly vs 7.7 +/- 0.6 ml h-1 kg-1 in the young) did not differ significantly between the two groups. Free VPA concentrations were significantly increased in the elderly. The clearance of the free drug (intrinsic clearance) was reduced from 127.0 +/- 12 ml h-1 kg-1 (control value in the young) to 77.7 +/- 5.5 ml h-1 kg-1 (P less than 0.02). Free VPA fraction was 9.5 +/- 0.6% in the elderly and 6.6 +/- 0.5% in the young (P less than 0.02). These findings suggest that the pharmacokinetic alterations of VPA in old age are complex and include at least two separate mechanisms: a decrease in plasma protein binding and a reduction of drug metabolizing capacity resulting in decreased clearance of free drug by the liver.